Mixed-lymphocyte reaction as a measure of immunological competence of lymphocytes from patients with Crohn's disease - Richens, Elizabeth R. (1974)
Peripheral blood lymphocytes from 12 patients with Crohn's disease and from a group of normal volunteers have been tested for transformation under stimulation of allogeneic cells in a mixed lymphocyte culture and by phytohaemagglutinin (PHA) in vitro. There was a significant depression of transformation in the mixed lymphocyte culture where lymphocytes from the Crohn's disease patients constituted the responding population. With PHA stimulation, no difference in transformation was seen between the patients and the control group. This is interpreted as indicating a depression in cellular immunity in Crohn's disease.